2016
DOI: 10.3389/fpls.2016.00487
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza Symbiosis Induces a Major Transcriptional Reprogramming of the Potato SWEET Sugar Transporter Family

Abstract: Biotrophic microbes feeding on plants must obtain carbon from their hosts without killing the cells. The symbiotic Arbuscular mycorrhizal (AM) fungi colonizing plant roots do so by inducing major transcriptional changes in the host that ultimately also reprogram the whole carbon partitioning of the plant. AM fungi obtain carbohydrates from the root cortex apoplast, in particular from the periarbuscular space that surrounds arbuscules. However, the mechanisms by which cortical cells export sugars into the apopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
153
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(163 citation statements)
references
References 67 publications
(117 reference statements)
4
153
1
5
Order By: Relevance
“…However, as an alternative scenario, it is feasible that an impaired function of H + ‐ATPases already affects an earlier step of sucrose transport. This is the efflux of sucrose from mesophyll cells into the apoplast what is carried out via SUGARS WILL EVENTUALLY BE EXPORTED TRANSPORTERS (SWEETs; Manck‐Götzenberger and Requena ). We hypothesize that these SWEET transporters are forced to reduce the export of sucrose from the mesophyll into the apoplast because of a reduced activity of H + /sucrose symporters.…”
Section: Discussionmentioning
confidence: 99%
“…However, as an alternative scenario, it is feasible that an impaired function of H + ‐ATPases already affects an earlier step of sucrose transport. This is the efflux of sucrose from mesophyll cells into the apoplast what is carried out via SUGARS WILL EVENTUALLY BE EXPORTED TRANSPORTERS (SWEETs; Manck‐Götzenberger and Requena ). We hypothesize that these SWEET transporters are forced to reduce the export of sucrose from the mesophyll into the apoplast because of a reduced activity of H + /sucrose symporters.…”
Section: Discussionmentioning
confidence: 99%
“…We also determined the expression of six SWEETs in the roots of M. truncatula after colonization with different root symbionts. SWEETs can not only catalyse the efflux of carbohydrates but also their uptake (Chen, ), and it has recently been suggested that members of the SWEET family could be involved in the symbiotic C flux (Kryvoruchko et al, ; Manck‐Götzenberger & Requena, ; Sugiyama et al, ). In contrast to MtSWEET11 that is specifically expressed in root nodules, none of the other SWEETs we tested showed a mycorrhiza‐restricted induction, but three of the SWEETs, MtSWEET1b , MtSWEET6 , and MtSWEET15d , were upregulated in AM roots compared with control roots (Figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to MtSWEET11 that is specifically expressed in root nodules, none of the other SWEETs we tested showed a mycorrhiza‐restricted induction, but three of the SWEETs, MtSWEET1b , MtSWEET6 , and MtSWEET15d , were upregulated in AM roots compared with control roots (Figure S5). According to the M. truncatula gene expression atlas (http://mtgea.noble.org/v3), MtSWEET1b and MtSWEET6 are highly expressed in arbusculated cells, and their putative orthologues StSWEET1a , StSWEET1b , and StSWEET 7a from potato also show high transcript levels in mycorrhizal roots (Manck‐Götzenberger & Requena, ). Although MtSWEET1b and MtSWEET6 are also highly expressed in rhizobial roots, the downregulation of both transporters in the tripartite interactions of Experiment 1 (Figure ), in which a suppression of the AM colonization by rhizobia was observed (Figure S2a), is an agreement with a potential role of both transporters for the sugar transport in arbusculated cells.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only a single study focused on SWEET transporters in mycorrhizal systems. Manck‐Gotzenberger and Requena () showed that the SWEET family in potato comprises 35 StSWEET and that 22 StSWEET genes were differentially regulated in response to AM symbiosis. Both plasma membrane (StSWEET7a and StSWEET12a) and tonoplastic (StSWEET2c) transporters are specifically relocalized in plant cells colonized by fungal arbuscules.…”
Section: Sugar Transport In Response To Biotic Factorsmentioning
confidence: 99%